Myeloid dendritic cells display downregulation of C-type lectin receptors and aberrant lectin uptake in systemic lupus erythematosus - Monrad, Seetha U (BioMed Central, 2008)
INTRODUCTION: There is a growing body of evidence implicating aberrant dendritic cell function as a crucial component in the immunopathogenesis of systemic lupus erythematosus. The purpose of the present study was to characterize the phagocytic capacity and expression of receptors involved in pathogen recognition and self-nonself discrimination on myeloid dendritic cells from patients with lupus. METHODS: Unstimulated or stimulated monocyte-derived dendritic cells were obtained from lupus patients and healthy control individuals, and expression of C-type lectin receptors (mannose receptor and dendritic cell-specific intercellular adhesion molecule-grabbing nonintegrin), complement-receptor 3 and Fcγ receptors was determined by flow cytometry. Dextran uptake by lupus and control dendritic cells was also assessed by flow cytometry. Serum IFNγ was quantified by ELISA, and uptake of microbial products was measured using fluorescently labeled zymosan. RESULTS: When compared with dendritic cells from healthy control individuals, unstimulated and stimulated lupus dendritic cells displayed significantly decreased dextran uptake and mannose receptor and dendritic cell-specific intercellular adhesion molecule-grabbing nonintegrin expression. Decreased expression of the mannose receptor was associated with high serum IFNγ levels, but not with maturation status or medications. Diminished dextran uptake and mannose receptor expression correlated with lupus disease activity. There were no differences between control and lupus dendritic cells in the expression of other pattern recognition receptors or in the capacity to uptake zymosan particles CONCLUSIONS: Lupus dendritic cells have diminished endocytic capacity, which correlates with decreased mannose receptor expression. While this phenomenon appears primarily intrinsic to dendritic cells, modulation by serum factors such as IFNγ could play a role. These abnormalities may be relevant to the aberrant immune homeostasis and the increased susceptibility to infections described in lupus.